Integración y conectividad urbano sectorial por medio de espacios socioculturales en el barrio Kennedy de Bucaramanga, Santander (2023)
The sectoral urban Integration and connectivity project through sociocultural spaces in the Kennedy neighborhood of Bucaramanga, Santander, arose from an urban need in the intervention area, the lack of pedestrian connections, congestion, pedestrians on the road without accessibility to platforms and the lack of public space, among others; that affects sociocultural and economic integration.